Menentukan Determinan Matriks Persegi Panjang Menggunakan Bahasa C++ - Diego Armando Piero; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — One study in matrix theory is determinant. Matrix determinants are widely used in solving matrix problems, such as: determining eigenvalues, systems solutions of linear and inverse equations. In determining a determinant of a square matrix is usually not easy especially with a large order matrix. The concept of determinant that has been known is generally true for square matrices. In this research, it will be studied about its development, which is about the determinant of non-square matrix (rectangular matrix). This research is a theoretical research through library research on determinant theories and programming theories. The purpose of this research is to determine the determinant of a rectangular matrix using C ++ language. The method used is the analysis of theories relevant to the problem of calculating rectangular matrix determinants using the C ++ language. The results of the study are produced programs that can determine the determinant of a rectangular matrix. Keywords — determinant, matrix, radic method, programming.